A membrane-free asymmetric faradaic capacitor deionization device and its application

By using an asymmetric Faraday capacitor deionization device composed of nitrogen-doped porous carbon-coated nanobismuth material and oxygen-rich transition metal carbide material, the problems of common ion expulsion effect and low capacity of traditional CDI devices in high-concentration salt solutions are solved, achieving efficient seawater desalination and low-cost desalination effects.

CN119833318BActive Publication Date: 2025-09-26ZHEJIANG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510035482.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-09-26
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

Traditional CDI devices have common ion expulsion effect and low capacity problems when treating high-concentration salt solutions. The volume expansion of Faraday positive electrode materials and insufficient specific capacity of negative electrode materials limit their application in fields such as seawater desalination.

Method used

A membraneless asymmetric Faraday capacitor deionization device is composed of nitrogen-doped porous carbon-coated nanobismuth material as the Faraday positive electrode and a transition metal carbide material rich in oxygen functional groups as the Faraday negative electrode, and the Faraday reaction is used to improve the adsorption capacity and cycle performance.

Benefits of technology

It broadens the concentration range of desalination applications and achieves stable and efficient desalination performance at high salt concentrations. The adsorption capacity is as high as 70 mg/g, the cycle performance retention rate is 90.0%, and no ion exchange membrane is required, which reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833318B_ABST
    Figure CN119833318B_ABST
Patent Text Reader

Abstract

The present invention discloses a membraneless asymmetric faraday capacitor deionization device, comprising a faraday anode and a faraday cathode. The faraday anode comprises a nitrogen-doped porous carbon-coated nanobismuth material (Bi@NCNF), and the faraday cathode comprises an oxygen-rich transition metal carbide material (MX-O). The device does not include an ion exchange membrane. The asymmetric faraday capacitor deionization device provided by the present invention is directly assembled from the aforementioned positive and negative electrodes, combining high adsorption capacity with long cycle performance. This effectively addresses the low capacity and low cycle times associated with conventional capacitor deionization devices and expands the concentration range for desalination applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitor deionization, and in particular to a membraneless asymmetric Faraday capacitor deionization device and its application. Background Art

[0002] Capacitive deionization (CDI) is an emerging desalination technology that has attracted much attention in recent years. Unlike other desalination methods, CDI devices do not extract water from salt solutions, but adsorb ions dissolved in salt solutions on the double-layer region at the interface between electrodes and solutions to achieve separation. Unlike traditional desalination technologies that require sophisticated membrane elements, high-pressure pumps or heat sources, CDI devices can operate at an external voltage of less than 2V under mild conditions such as low osmotic pressure and room temperature. Compared with other desalination technologies, they have the advantages of low cost and environmental protection and energy saving. At the same time, the CDI device can selectively extract some ions in the solution, giving it a variety of potential application scenarios including seawater desalination, hard water softening, heavy metal salt purification, industrial, agricultural and domestic water decontamination, nuclear power plant wastewater treatment, and precious metal ion resource recovery.

[0003] The working components of a CDI device primarily consist of a positive electrode and a negative electrode, which adsorb anions and cations from the solution, respectively. Their adsorption performance is directly related to the performance and matching of the positive and negative electrodes. Limited by the low ion adsorption capacity of conventional carbon-based electrode materials, the practical application of CDI still faces numerous challenges. For example, in seawater desalination, as the salt concentration of the treated solution increases, the negative impact of the common ion expulsion effect on carbon-based electrode materials inevitably becomes more pronounced, leading to a sharp decrease in charging efficiency and even inability to perform desalination properly. Therefore, conventional CDI is currently only capable of desalinating extremely low-concentration brackish water (<3000 mg / L), far from achieving medium- to high-concentration brackish water (≥3000 mg / L) or even realistic seawater concentrations (~35,000 mg / L). Furthermore, the inherently low capacity of conventional carbon-based electrodes also contributes significantly to the unsatisfactory adsorption capacity of CDI devices. Even the various new electrodes developed in this field still have considerable room for improvement. It's worth noting that while some CDI devices have further improved their applicability and performance by incorporating ion exchange membranes, the high cost of these membrane elements presents a new barrier to widespread adoption. Therefore, developing and matching new cathode and anode electrode materials with high ion selectivity, high capacity, and long cycle performance is crucial for the further development of membraneless CDI.

[0004] In recent years, a faradaic deionization (FDI) based on battery materials has received widespread attention. Compared with the working principle of pure physical adsorption of carbon-based electrodes, faradaic electrodes have more types of reaction mechanisms, such as ion intercalation, redox, conversion reactions, etc. More types of reaction mechanisms give faradaic electrodes higher desalination performance and better ion selectivity, and eliminate the possibility of common ion expulsion effects from the working principle. However, to date, the development of most faradaic materials has been limited to negative electrode materials, that is, the removal of cations (especially sodium ions), while research on faradaic positive electrode materials for anions is relatively rare. For example, the Chinese patent with publication number CN116959895A discloses a Prussian blue analogue electrode for hybrid capacitive deionization, in which the Prussian blue analogue adsorbs sodium ions as a faradaic capacitor and uses activated carbon as a double-layer capacitor to adsorb chloride ions, thereby removing sodium chloride and achieving the purpose of desalination. And Chinese patent publication number CN113077996A discloses a preparation method and application of a sodium vanadium oxyfluorophosphate / graphene composite electrode material. This method is based on the principle of charge storage by Faraday capacitance and double-layer capacitance. In a flowing electrode capacitive deionization device, under a certain voltage, one electrode uses a sodium vanadium oxyfluorophosphate / graphene composite flowing electrode slurry as a Faraday capacitor to adsorb sodium ions, while the other electrode uses activated carbon as a double-layer capacitor flowing electrode slurry to adsorb chloride ions, thereby removing sodium chloride and achieving the purpose of desalination.

[0005] On the other hand, the performance matching of the positive and negative electrode materials of FDI devices has not received enough attention. The common volume expansion problem of Faraday positive electrode materials is the culprit for the rapid degradation of cycle performance, and the specific capacity of Faraday negative electrode materials themselves still has a lot of room for improvement, which seriously affects the further development of FDI.

[0006] Therefore, how to develop high-performance Faraday positive electrode materials and high-performance Faraday negative electrode materials separately and assemble them into an asymmetric system to form a new FDI device with both high adsorption capacity and long cycle performance is of great significance to the development and application of FDI and even CDI. Summary of the Invention

[0007] The purpose of the present invention is to provide a membrane-free asymmetric faradaic capacitor deionization device, which has both high adsorption capacity and long cycle performance when used in desalination, and expands the concentration range of desalination applications.

[0008] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0009] A membraneless asymmetric faradaic capacitive deionization device comprises a faradaic anode and a faradaic cathode, wherein the faradaic anode comprises a nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF, and the faradaic cathode comprises an oxygen-rich transition metal carbide material MX-O. The device does not comprise an ion exchange membrane.

[0010] The membraneless asymmetric Faraday capacitor deionization device provided by the present invention is directly assembled by the above-mentioned Faraday positive electrode and Faraday negative electrode without including any ion exchange membrane. It has both high adsorption capacity and long cycle performance, effectively solving the problems of low capacity and low cycle number existing in traditional capacitor deionization devices.

[0011] The preparation method of the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF comprises: using bismuth nitrate pentahydrate, pyrazole-3,5-dicarboxylic acid and camphoric acid as raw materials, performing a hydrothermal reaction to obtain a precursor; and calcining the precursor to obtain Bi@NCNF.

[0012] The feed ratio of the bismuth nitrate pentahydrate, pyrazole-3,5-dicarboxylic acid and camphoric acid is: 0.8 g of bismuth nitrate pentahydrate (purity ≥99.0%), 0.35 g of pyrazole-3,5-dicarboxylic acid (purity ≥99.0%) and 0.4 g of camphoric acid (purity ≥99.0%).

[0013] The temperature of the hydrothermal reaction is 120° C., and the reaction time is 96 hours.

[0014] The calcination temperature is 600-800°C.

[0015] Preferably, the calcination temperature is 600-700° C. The size and typical porous hollow morphology of the nano-bismuth in Bi@NCNF obtained under such calcination conditions are more conducive to improving the adsorption capacity of the assembled FDI device.

[0016] Preferably, the size of the nano-bismuth in the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF is 30 nm to 100 nm.

[0017] The Faraday positive electrode uses Bi@NCNF as an active material, which is ground and mixed with conductive carbon black and PVDF powder in N-methylpyrrolidone, sprayed onto conductive carbon paper, and dried for use as a positive electrode.

[0018] The preparation method of the oxygen-rich transition metal carbide material MX-O comprises: mechanically mixing titanium aluminum carbide, hydrochloric acid and lithium fluoride to react to obtain a transition metal carbide suspension as a precursor material; and subjecting the precursor material to room temperature plasma discharge activation treatment under a hydrogen atmosphere to obtain the oxygen-rich transition metal carbide suspension.

[0019] The feeding ratio of the titanium aluminum carbide, hydrochloric acid and lithium fluoride is: 1 gram of titanium aluminum carbide (purity ≥99.0%), 20 milliliters of hydrochloric acid (concentration 9.0 mol / L), and 1 gram of lithium fluoride (purity ≥99.0%).

[0020] In the plasma discharge activation treatment, the activation treatment time for a precursor material with a mass of 50 mg is 3-5 minutes.

[0021] Preferably, the processing time of the precursor material is 3-5 minutes, so that the assembled FDI device can have a higher sodium ion adsorption capacity.

[0022] Among them, a transition metal carbide suspension rich in oxygen functional groups is vacuum filtered into a thin film and directly used as a negative electrode.

[0023] The present invention also provides an application of the membraneless asymmetric Faraday capacitor deionization device in desalination. The concentration of the sodium chloride solution is 2000-35000 mg / L.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] 1. The FDI device of the present invention broadens the concentration range for capacitive deionization in seawater desalination. For example, the device can still perform stable and efficient desalination in a high-salt sodium chloride solution with a concentration of 5000 mg / L. Conventional CDI devices, however, are limited to desalination of brackish water with a concentration of less than 3000 mg / L due to the common ion expulsion effect.

[0026] 2. The FDI device of the present invention exhibits a high adsorption capacity: for example, in a desalination test in a 5000 mg / L sodium chloride solution under a constant charging voltage of 1.2 V for 60 minutes, an optimal adsorption capacity of up to 70 mg / g was achieved.

[0027] 3. The FDI device of the present invention exhibits excellent cycling performance: for example, in a continuous desalination test in a 5000 mg / L sodium chloride solution under a constant charge voltage of 1.2 V, a constant discharge voltage of 1.2 V, and a single adsorption / desorption cycle duration of 60 minutes, the capacity retention rate after 100 cycles was as high as 90.0%.

[0028] 4. The FDI device of the present invention is simple to assemble and does not contain additional components such as ion exchange membranes. It is directly assembled from the above-mentioned positive electrode and negative electrode, and has the potential for further promotion and use in terms of cost and process. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1Transmission electron microscopy (TEM) images of nano-bismuth prepared in Examples 1-3 show porous bismuth structures on the surface of carbon nano-bundles.

[0030] Figure 2 This is a high-resolution transmission electron microscopy (HRTEM) image of the porous carbon-coated nanobismuth prepared in Example 1, showing two typical morphologies: a carbon coating layer and a hollow area.

[0031] Figure 3 This is an energy dispersive spectrometer (EDS) image of the nitrogen-doped porous carbon-coated nanobismuth prepared in Example 1. It is observed that the nitrogen-doped porous carbon-coated nanobismuth is composed of four elements: bismuth, carbon, nitrogen, and oxygen;

[0032] Figure 4 The X-ray photoelectron spectroscopy (XPS) diagrams of the transition metal carbides prepared in Examples 4-6 and Comparative Example 1 show changes in the content of oxygen functional groups in the transition metal carbides;

[0033] Figure 5 Electrochemical quartz crystal microbalance (EQCM) tests of the transition metal carbides prepared in Examples 4-6 and Comparative Example 1 demonstrated changes in the adsorption capacity of the transition metal carbides for sodium ions;

[0034] Figure 6 The cyclic voltammetry curve of the nano-bismuth prepared in Example 1-3 in a 1 mol / L sodium chloride solution system;

[0035] Figure 7 Cyclic voltammetry curves of the transition metal carbides prepared in Examples 4-6 and Comparative Example 1 in a 1 mol / L sodium chloride solution system;

[0036] Figure 8 Schematic diagram of the membrane-less asymmetric Faraday capacitor deionization device provided by the present invention;

[0037] Figure 9 The adsorption capacity curves of the asymmetric FDI of each combination of Examples 1-3, Example 4, and Comparative Example 1 in a 5000 mg / L sodium chloride solution are shown;

[0038] Figure 10 The cycling performance of the asymmetric FDI in a sodium chloride solution with a concentration of 5000 mg / L is shown in FIG.

[0039] Figure 11 The adsorption capacity curves of the asymmetric FDI devices assembled in Example 1 and Example 4 in sodium chloride solutions of different concentrations are shown. DETAILED DESCRIPTION

[0040] Example 1: 0.8 g of bismuth nitrate pentahydrate (purity ≥ 99.0%), 0.35 g of pyrazole-3,5-dicarboxylic acid (purity ≥ 99.0%), and 0.4 g of camphoric acid (purity ≥ 99.0%) were mechanically mixed with 10 ml of deionized water, 10 ml of N-methylpyrrolidone (purity ≥ 99.0%), and 10 ml of acetamide (purity ≥ 99.0%). The mixture was reacted in a hydrothermal autoclave at 120°C for 96 hours. The precursor material prepared by the above reaction was washed multiple times with ethanol by centrifugation, dried thoroughly, and then heated at 700°C for 2 hours under an argon atmosphere. After cooling to room temperature, a nitrogen-doped porous carbon-coated nano-bismuth electrode material was obtained. Nano-bismuth is used as the active material, ground and mixed with conductive carbon black (purity ≥99.0%) and PVDF powder (purity ≥99.0%) in N-methylpyrrolidone in a mass ratio of 8:1:1, and finally sprayed onto conductive carbon paper and dried for use as the positive electrode, namely Bi@NCNF-700.

[0041] Example 2: The difference from Example 1 is that when preparing the nitrogen-doped porous carbon-coated nano-bismuth electrode material, the heating temperature under argon atmosphere is changed from 700°C to 600°C to obtain the positive electrode, namely Bi@NCNF-600.

[0042] Example 3: The difference from Example 1 is that when preparing the nitrogen-doped porous carbon-coated nano-bismuth electrode material, the heating temperature under argon atmosphere is changed from 700°C to 800°C to obtain the positive electrode, namely Bi@NCNF-800.

[0043] The electrode material morphology obtained in Example 1-3 is a nitrogen-doped porous carbon-coated nano-bismuth material ( Figure 1 ).from Figure 1 It can be seen that the size and content of nanobismuth in different examples are different: in Example 1, it can be observed that the nanobismuth exhibits agglomeration characteristics, with large-sized nanoparticles (large size greater than or equal to 100 nm) and a high bismuth content; in Example 2, it can be observed that the nanobismuth exhibits uniform dispersion characteristics, the nanoparticle size is reduced, and the spherical characteristic morphology of the nanobismuth can be clearly observed (medium size between 30 nm and 100 nm, and the nanobismuth is evenly dispersed), and the material still has a high bismuth content at this time; in Example 3, it can be observed that the content of nanobismuth decreases sharply, and only a small amount of nanobismuth with a smaller size (small size less than or equal to 30 nm) exists.

[0044] The nano-bismuth material obtained in Example 1 has a typical porous carbon coating morphology ( Figure 2 ).from Figure 2 It can be seen that there is a stacked carbon coating around the nano-bismuth, which is beneficial to electron transmission and enhances the conductivity and structural stability of the nano-bismuth material; Figure 2It can be seen that there are porous hollow areas between the carbon coating layers, which are conducive to ion storage and increase the specific surface area and ductility of the nanobismuth material.

[0045] The nano-bismuth material obtained in Example 1 is composed of various elements such as bismuth, carbon, nitrogen, and oxygen ( Figure 3 ).from Figure 3 It can be seen that the bismuth element is distributed in a spherical shape, proving that bismuth exists in the form of nanoparticles; carbon, nitrogen and oxygen elements are evenly distributed, proving that the material coating the nano-bismuth is nitrogen-doped porous carbon.

[0046] Example 4: 1 gram of titanium aluminum carbide (purity ≥99.0%), 20 milliliters of hydrochloric acid (concentration 9.0 mol / L), and 1 gram of lithium fluoride (purity ≥99.0%) were mechanically mixed and stirred continuously at 35°C for 24 hours. The mixture was then centrifuged and washed several times with deionized water until the pH of the solution was close to 5. The mixture was first ultrasonicated in an ice bath for 1 hour, then centrifuged at 3500 rpm for 1 hour, and the supernatant was collected to obtain a transition metal carbide suspension. The precursor material prepared by the above reaction was subjected to room temperature plasma discharge activation treatment at a voltage of 50 V in a hydrogen atmosphere. 50 mg of the precursor material (10 milliliters of a precursor solution with a concentration of 5 mg / ml) was activated for 5 minutes to obtain a transition metal carbide suspension rich in oxygen functional groups. The suspension was finally vacuum filtered to form a thin film, which was directly used as a negative electrode, i.e., MX-O2.

[0047] Comparative Example 1: The difference from Example 4 is that when preparing the transition metal carbide rich in oxygen functional groups, the plasma discharge activation time is changed from 5 min to 0 min, thereby obtaining a negative electrode, namely, Pristine MX.

[0048] Example 5: The difference from Example 4 is that when preparing the transition metal carbide rich in oxygen functional groups, the plasma discharge activation time is changed from 5 min to 3 min to obtain the negative electrode, namely, MX-O1.

[0049] Example 6: The difference from Example 4 is that when preparing the transition metal carbide rich in oxygen functional groups, the plasma discharge activation time is changed from 5 min to 10 min to obtain the negative electrode, namely, MX-O3.

[0050] The electrode materials obtained in Examples 4-6 and Comparative Example 1 are transition metal carbide materials ( Figure 4 ).from Figure 4 It can be seen that the oxygen functional groups (C-Ti-O x ) and hydroxyl functional groups (C-Ti-(OH) x) content and conversion relationship: Comparative Example 1 has the highest hydroxyl functional group (C-Ti-(OH) x ) content (i.e. 34.3%) and the relatively lowest oxygen functional group (C-Ti-O x ) content (i.e. 11.8%), the hydroxyl functional groups (C-Ti-(OH) x ) content gradually decreases, oxygen functional groups (C-Ti-O x ) content gradually increased, proving that with the increase of discharge activation time, the hydroxyl functional group (C-Ti-(OH) x ) will gradually transform into oxygen functional groups (C-Ti-O x ), the relatively lowest hydroxyl functional group (C-Ti-(OH) x ) content (i.e. 18.3%) and the relatively highest oxygen functional group (C-Ti-O x ) content (i.e. 27.7%).

[0051] The electrode materials obtained in Examples 4-6 and Comparative Example 1 are transition metal carbide materials ( Figure 5 ).from Figure 5 It can be seen that the adsorption capacity of the transition metal carbide materials of Examples 4-6 and Comparative Example 1 for sodium ions during charging is compared: under the same charging charge, Example 4 has the relatively highest sodium ion adsorption mass (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 158.1ng), the sodium ion adsorption mass of Example 5 is slightly reduced (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 93.3ng), and the sodium ion adsorption mass of Example 6 is slightly reduced (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 77.9ng). Comparative Example 1 has the relatively lowest sodium ion adsorption mass (that is, when the total charging charge is -0.3mC, the sodium ion adsorption mass is 51.7ng).

[0052] 1. Electrochemical performance test of positive and negative electrodes:

[0053] Cyclic voltammetry was performed using an AutoLAB electrochemical workstation with a three-electrode system (silver / silver chloride reference electrode, platinum counter electrode) and a 1 mol / L sodium chloride solution as the electrolyte. The voltage window for the nano-bismuth electrode material was -1.2 to 0.8 V, with a scan rate of 5 mV / s; the voltage window for the transition metal carbide electrode material was -1 to 0 V, with a scan rate of 5 mV / s.

[0054] Figure 6 The cyclic voltammetry curve of the nitrogen-doped porous carbon-coated nano-bismuth electrode material prepared in Example 1-3 in a 1 mol / L sodium chloride solution system; Figure 6It can be seen that Examples 1-3 all exhibit the typical oxidation and reduction peak characteristics of bismuth materials. The cyclic voltammetry curve area of ​​Example 1 is larger than that of Examples 2-3, indicating that the electrochemical performance of Bi@NCNF-700 is superior to that of Bi@NCNF-600 and Bi@NCNF-800 (the specific capacities of Examples 1-3 are 398 F / g, 262 F / g, and 152 F / g, respectively, indicating that Example 1 performs better than Example 2 and Example 3).

[0055] Figure 7 Cyclic voltammetry curves of the transition metal carbides prepared in Examples 4-6 and Comparative Example 1 in a 1 mol / L sodium chloride solution system; Figure 7 It can be seen that Examples 4-6 and Comparative Example 1 all exhibit typical pseudocapacitive shape characteristics. The cyclic voltammetry curve area of ​​Example 4 is larger than that of Examples 5-6 and Comparative Example 1, indicating that the electrochemical performance of MX-O2 is superior to that of MX-O1, MX-O3, and Pristine MX (the specific capacities of Examples 4-6 and Comparative Example 1 are 63.7 F / g, 59.4 F / g, 49.6 F / g, and 26.6 F / g, respectively, indicating that Example 4 performs better than Example 6, Example 5, and Comparative Example 1).

[0056] 2. Test of electrosorption performance of asymmetric FDI:

[0057] In order to test the adsorption effect of the present invention on the desalination of brackish water, the examples were assembled into different systems of membrane-free asymmetric FDI and the corresponding adsorption performance test experiments were carried out ( Figure 8 ):

[0058] System 1: Example 1 and Example 4 were assembled into an asymmetric FDI device, and desalination test was carried out in a sodium chloride solution with a concentration of 5000 mg / L. The charging conditions were constant voltage 1.2V, charging for 30 minutes, and the discharging conditions were constant voltage -1.2V, discharging for 30 minutes ( Figure 9 ), long cycle performance test is to test 100 cycles continuously ( Figure 10 ).

[0059] System 2: Example 2 and Example 4 were assembled into an asymmetric FDI device, and desalination test was carried out in a sodium chloride solution with a concentration of 5000 mg / L. The charging conditions were constant voltage 1.2V, charging for 30 minutes, and the discharging conditions were constant voltage -1.2V, discharging for 30 minutes ( Figure 9 ).

[0060] System 3: Example 3 and Example 4 were assembled into an asymmetric FDI device, and desalination test was carried out in a sodium chloride solution with a concentration of 5000 mg / L. The charging conditions were constant voltage 1.2V, charging for 30 minutes, and the discharging conditions were constant voltage -1.2V, discharging for 30 minutes ( Figure 9 ).

[0061] System 4: Example 1 and Comparative Example 1 were assembled into an asymmetric FDI device, and desalination tests were performed in a sodium chloride solution with a concentration of 5000 mg / L. The charging conditions were constant voltage 1.2 V, charging for 30 minutes, and the discharging conditions were constant voltage -1.2 V, discharging for 30 minutes ( Figure 9 ).

[0062] from Figure 9 It can be seen that the asymmetric FDI under different systems has different adsorption properties. The adsorption amounts measured in systems 1 to 4 are 71.7 mg / g, 50.9 mg / g, 41.3 mg / g, and 55.2 mg / g, respectively. That is, system 1 is better than system 4, better than system 2, and better than system 3. That is, in system 1, Example 1 and Example 4 are assembled into an asymmetric FDI device, which has the best desalination adsorption performance.

[0063] from Figure 10 It can be seen that when the system 1 was subjected to a long cycle performance test for 100 consecutive times, the desalination adsorption performance did not show obvious attenuation, and the desalination adsorption performance of a single cycle was stably maintained at around 70 mg / g, proving that the assembly of Example 1 and Example 4 into an asymmetric FDI device in System 1 has good cycle performance.

[0064] 3. Example 1 and Example 4 were assembled into an asymmetric FDI device, and desalination tests were performed in sodium chloride solutions with concentrations of 35000 mg / L, 20000 mg / L, 10000 mg / L, 5000 mg / L, and 2000 mg / L, respectively. The charging conditions were constant voltage 1.2 V, charging for 30 minutes, and the discharging conditions were constant voltage -1.2 V, discharging for 30 minutes ( Figure 11 ), the measured adsorption amounts are 124.74 mg / g, 114.31 mg / g, 90.70 mg / g, 71.74 mg / g and 37.82 mg / g, respectively.

Claims

1. Application of a membraneless asymmetric Faraday capacitor deionization device in desalination, characterized in that: The device performs desalination in a sodium chloride solution with a concentration of 2000-35000 mg / L; The device includes a Faraday positive electrode and a Faraday negative electrode, wherein the Faraday positive electrode includes a nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF, and the Faraday negative electrode includes a transition metal carbide material MX-O rich in oxygen functional groups, and the device does not include an ion exchange membrane; The preparation method of the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF comprises: using bismuth nitrate pentahydrate, pyrazole-3,5-dicarboxylic acid and camphoric acid as raw materials, performing a hydrothermal reaction to obtain a precursor; calcining the precursor to obtain Bi@NCNF; and the calcination temperature is 600-800°C.

2. Application of the membraneless asymmetric faradaic capacitor deionization device in desalination according to claim 1, characterized in that: The Faraday positive electrode uses Bi@NCNF as an active material, which is ground and mixed with conductive carbon black and PVDF powder in N-methylpyrrolidone, sprayed onto conductive carbon paper, and dried for use as a positive electrode.

3. Application of the membraneless asymmetric faradaic capacitor deionization device in desalination according to claim 1, characterized in that: The preparation method of the oxygen-functional group-rich transition metal carbide material MX-O includes: mechanically mixing titanium aluminum carbide, hydrochloric acid and lithium fluoride to react to obtain a transition metal carbide suspension as a precursor material; subjecting the precursor material to room temperature plasma discharge activation treatment in a hydrogen atmosphere to obtain a transition metal carbide suspension rich in oxygen functional groups; in the plasma discharge activation treatment, the activation treatment time is 3-10 minutes.

4. The application of the membraneless asymmetric faradaic capacitor deionization device in desalination according to claim 3, characterized in that: In the plasma discharge activation treatment, the activation treatment time for a precursor material with a mass of 50 mg is 3-5 minutes.

5. Application of the membraneless asymmetric Faraday capacitor deionization device in desalination according to claim 4, characterized in that: The transition metal carbide suspension rich in oxygen functional groups is vacuum filtered into a thin film and directly used as a negative electrode.

6. Application of the membraneless asymmetric faradaic capacitor deionization device in desalination according to claim 1, characterized in that: The size of the nano-bismuth in the nitrogen-doped porous carbon-coated nano-bismuth material Bi@NCNF is 30 nm to 100 nm.

Citation Information

Patent Citations

  • Preparation method and application of sodium vanadium oxyfluorophosphate / graphene composite electrode material

    CN113077996A

  • Preparation method and application of Prussian blue analogue electrode applied to hybrid capacitive deionization

    CN116959895A

  • Preparation method of room-temperature plasma activated MXene electrode material and product and application of room-temperature plasma activated MXene electrode material

    CN117153568A